(untitled) (Research, Society and Development, 2021)
Orbital fractures occur with considerable frequency and when there is involvement of its walls, changes in orbital volume are usually observed, resulting in several clinical changes. The objective of this study is to correlate the increase in orbital volume, post-trauma in the face, with the clinical changes observed, emphasizing the influence of these variables on decision making regarding the most appropriate therapeutic intervention. A bibliographic survey was carried out in the main online databases, using the descriptors: Orbit, Bone Fractures, Tomography and Maxillofacial Surgery, covering complete articles of research, review, and also, case reports, published in the last few 5 years (2015-2020), in English, Portuguese and Spanish. Through the study, it became clear that orbital fractures represent 40% of all facial fractures, and this percentage may increase when other articulated bones are involved. There was a positive correlation between the increase in orbital volume and the occurrence of some clinical changes. Regarding the choice of the appropriate treatment for the correction of deformities, it was understood that clinical and radiographic characteristics must be observed, with diplopia, dystopia, enophthalmia, exolftalmia, ophthalmoplegia and nerve injury being the main clinical changes. In this way, it is concluded that the volumetric increase directly influences the clinical repercussions after trauma in the face, and therapeutic decisions should be considered in the process, which can be surgical or conservative.